Effects of high-pressure homogenization on physicochemical and functional properties of enzymatic hydrolyzed soybean protein concentrate - Liang, Yaru; Guo, Yanan; Zheng, Yuxuan; Liu, Sibo; Cheng, Tianfu; Zhou, Linyi; Guo, Zengwang (Frontiers in Nutrition, 2022)
This paper investigates the effect on the physicochemical and functional properties of soybean protein concentrate (SPC) by using Alcalase protease and high-pressure homogenization (HPH) (0, 20, 40, 60, 80, 100 MPa) for the combined modification. The results showed that the degree of hydrolysis of SPC was 4.1% and the antigen protein was degraded after Alcalase hydrolysis, when the homogenization pressure(HP) was 60 Mpa, the particle size of the SPC was the smallest, the zate potential absolute value up to 33.45 mV, the secondary structure has the lowest β-sheet content, the highest random coil content, and the highest surface hydrophobicity (H0), the size of protein fragments on the microstructure surface is the smallest, the lowest denaturation temperature (Td) and enthalpy (△H) are 72.59°C and 1.35 J/g, the highest solubility is 80.54%, and the highest water and oil holding capacities are 7.73 g/g and 6.51g/g, respectively. The best emulsifying activity and emulsifying stability were 43.46 m2/g and 190.35 min, the most even distribution of emulsion droplets. This indicates that the HPH treatment destroys the structure of enzymatic hydrolyzed SPC, changes its physicochemical properties, and improves its functional properties. In this study, SPC was modified by HPH and enzyme combined treatment, in order to improve the functionality and application range of SPC, and provide a theoretical basis for its high-value utilization in the food field.